Multiple links between shade avoidance and auxin networks - Iglesias, María José (2018)
Auxin has emerged as a key player in the adjustment of plant morphology to the challenge imposed by variable environmental conditions. Shade-Avoidance responses, including the promotion of stem and petiole growth, leaf hyponasty, and the inhibition of branching, involve an intimate connection between light and auxin signalling. Low activity of photo-sensory receptors caused by the presence of neighbouring vegetation enhances the activity of PHYTOCHROME INTERACTING FACTORs (PIFs), which directly promote the expression of genes involved in auxin biosynthesis, conjugation, transport, perception, and signalling. In seedlings, neighbour signals increase auxin levels in the foliage, which then moves to the stem, where it reaches epidermal tissues to promote growth. However, this model only partially accounts for shade-Avoidance responses (which may also occur in the absence of increased auxin levels), and understanding the whole picture will require further insight into the functional significance of the multiple links between shade and auxin networks.